2016
DOI: 10.1371/journal.pone.0163072
|View full text |Cite
|
Sign up to set email alerts
|

Three Dimensional Human Neuro-Spheroid Model of Alzheimer’s Disease Based on Differentiated Induced Pluripotent Stem Cells

Abstract: The testing of candidate drugs to slow progression of Alzheimer’s disease (AD) requires clinical trials that are lengthy and expensive. Efforts to model the biochemical milieu of the AD brain may be greatly facilitated by combining two cutting edge technologies to generate three-dimensional (3D) human neuro-spheroid from induced pluripotent stem cells (iPSC) derived from AD subjects. We created iPSC from blood cells of five AD patients and differentiated them into 3D human neuronal culture. We characterized ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
145
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(150 citation statements)
references
References 42 publications
2
145
0
Order By: Relevance
“…To date, several research groups have reported the usage of iPSCs in AD modeling, which provide a proof-of-principle for modeling patient-specific AD pathology in human brain-like environment [2530, 3742, 48, 49, 52, 53]. These patient-derived AD neurons were mainly generated from FAD patients but also a few from sAD patients.…”
Section: Recapitulating Aβ Pathology In Human Ipsc-derived Neuronsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, several research groups have reported the usage of iPSCs in AD modeling, which provide a proof-of-principle for modeling patient-specific AD pathology in human brain-like environment [2530, 3742, 48, 49, 52, 53]. These patient-derived AD neurons were mainly generated from FAD patients but also a few from sAD patients.…”
Section: Recapitulating Aβ Pathology In Human Ipsc-derived Neuronsmentioning
confidence: 99%
“…In general, only a handful of SAD patients showed the increased Aβ levels, which have not been replicable between patients [3841, 49, 50]. It is not easy to determine whether these variabilities stem from the presence of multiple genetic variants or differential neuronal differentiation conditions due to the lack of isogenic control cell lines.…”
Section: Recapitulating Aβ Pathology In Human Ipsc-derived Neuronsmentioning
confidence: 99%
“…In a different approach, Lee et al used a combination of differentiated iPSC and 3D neurospheroids to perform a drug screening in an AD model. [144] iPSC derived from AD patients were differentiated and treated with β -site amyloid precursor protein cleaving enzyme 1 (BACE1) inhibitors to assess their effect on A β levels. Interestingly, they found that higher concentrations of the inhibitor were needed in order to lower A β in neurospheroids model, likely due to the diminished surface exposure of neurospheroids, lower diffusion rate and more time required for the inhibitor to penetrate into the spheroids.…”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%
“…This model represent a more physiologically relevant system to the human brain compared to other current cell culture systems and allows high-throughput quantification in addition to proteomics analyses. [144] …”
Section: Recapitulating the Human Brain Pathophysiologymentioning
confidence: 99%
“…These types of cell models are important, because they can be made from human cells, which are easier to get and cheaper to use than cells from animals. In fact, a recent study used iPSCs from patients with Alzheimer's disease and made them into a three-dimensional cell model [5]. The researchers showed that there is a buildup of abnormal protein in the cell model that is just like what happens in the in vivo disease.…”
Section: How Are Neurons Made From Stem Cells Being Used?mentioning
confidence: 99%